ANALISIS KUALITAS LAYANAN APLIKASI PRESENSI PKL SISWA SMKN 1 MADIUN 2024 MENGGUNAKAN METODE SERVQUAL - Widianto, Gilang Firmansyah Widianto; Dwi Wahyuni, Evi; Rizki , Didih (P3M Politeknik Negeri Banjarmasin, 2025)
This research analyzes the quality of the PKL Presence Application service used by students at SMK Negeri 1 Madiun using the SERVQUAL method. The SERVQUAL method measures service quality based on five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. This research aims to determine students' perceptions of the quality of application services and analyze the influence of these dimensions on user satisfaction. Data was collected through a questionnaire distributed to class XII students in the Audio Video department as application users. The research results show that students' perceptions of the application are good, and the Responsiveness and Empathy dimensions have a significant influence on user satisfaction, while the Tangibles, Reliability and Assurance dimensions do not have a significant influence. Recommended improvements include improving the application interface design to make it more user-friendly and modern to increase the Tangibles dimension, bug fixes to increase Reliability, as well as implementing additional security features such as two-factor authentication to strengthen Assurance. With this recommendation for improvement, it is hoped that it will be accepted by application developers or schools to increase user satisfaction in the quality of the SMKN 1 Madiun PKL attendance application service.